2017
DOI: 10.2166/ws.2017.156
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of water budget prediction accuracy using ARIMA models

Abstract: The European Union Water Framework Directive obliges each country to monitor the groundwater level as it is an important source of drinking water, but also an important part of agriculture. A water budget is used for assessing the accuracy of the groundwater level determination. The computations of the water budget are based on evapotranspiration and the state of land surface hydrosphere. On the basis of the determined water budget, statistics and the prognosis for the next 12 months can be computed. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…It comes in a variety of forms like AR, MA, or combination of AR and MA, referred to as autoregressive moving average (ARMA) or seasonal autoregressive integrated moving average (SARIMA) [22,23]. It has been found in literature that only a few attempts have been undertaken to predict the WL using the SARIMA model, such as predictions of lake water levels [24] and groundwater levels [25]. Whereas, the SARIMA model has the advantage of requiring few model parameters to describe time series, that show non-stationarity both within and through seasons [26].…”
Section: Introductionmentioning
confidence: 99%
“…It comes in a variety of forms like AR, MA, or combination of AR and MA, referred to as autoregressive moving average (ARMA) or seasonal autoregressive integrated moving average (SARIMA) [22,23]. It has been found in literature that only a few attempts have been undertaken to predict the WL using the SARIMA model, such as predictions of lake water levels [24] and groundwater levels [25]. Whereas, the SARIMA model has the advantage of requiring few model parameters to describe time series, that show non-stationarity both within and through seasons [26].…”
Section: Introductionmentioning
confidence: 99%
“…Predicting dynamic water level variations using ARIMA and sequential Gaussian simulation (SGS) was the focus of (Takafuji et al, 2019). Groundwater fluctuation patterns in the Warangal district were assessed using the ARIMA and parametric Mann-Kendal (MK) methods (Satish Kumar & Venkata Rathnam, 2019) Multiple research (Birylo et al, 2018) (Gibrilla et al, 2018) used the ARIMA model to forecast yearly, monthly, and seasonal GWL. Forecasting GWL in a complex and uncertain environment can be made easier with the utilization of ANN algorithms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The AR part describes the relationship between present and past observations, the MA part represents the autocorrelation structure of error, and the I part represents the differencing level of the series [65]. ARIMA is one of the most powerful and successful linear statistical models for time series forecasting [66]. Research made by Valipour and Banihabib [67] showed that in comparison with ARMA (autoregressive moving average), the ARIMA model is better than ARMA because it can make time-series stationery in the training and forecasting phase [68].…”
Section: Forecasting Using Automated Arima Toolmentioning
confidence: 99%